A Companion to Environmental Geography - Castree, Noel [et. al.] (Malden Blackwell Pub., 2016)
This volume presents more than 30 newly commissioned essays by leading scholars that provide a summary of the state of the art in environmental geography and look ahead to future research
Include Maps and Index